HEMOTOLOGICAL OF Clarias gariepinus THAT WERE GIVEN WITH VACCINE TO PREVENT Motile Aeromonas Septicemia DISEASE - Deny Triyatna; Iesje Lukistyowati; Morina Riauwaty (Berkala Perikanan Terubuk, 2019)
The vaccine is one of the alternative to improve infection of the immunity system. The purpose of this research was to understand the hematological of (Clarias gariepinus) that were with given Aeromonas hydrophila vaccine. This research was conducted on 14 April until 2 June 2019. The method was an experimental method with a Completely Randomized Design (CRD) five treatments and three times replication. The treatments appliced were: Kn: (The fishes that were not given with vaccine and infected by Aeromonas hydrophila), Kp: (The fishes that were not given vaccine and was infected by Aeromonas hydrophila, P1: Soaked with vaccine dose 1 ml/10 L, P2: Soaked with vaccine dose 1 ml/10 L, P3: (Dipping with vaccine dose 1 ml/10 L. Dipping with the vaccine is done for 15 minutes. Clarias gariepinus at average 8-10 cm TL. After 23 day, the fishes were infected with Aeromonas hydrophila, the purpose of which was to determine imumunity of fish. The results show that the vaccine for 15 minutes is able to prevent the Motile Aeromonas Septicemia (MAS) disease. The were range total erythrocyte is 2,29×106 sel/mm3, hemoglobin 12,60 g/dl, Leukocytes Differensial (Lymphocytes 71,33%, Monocytes 16,66% and Neutrophils 12,00%) and Survival Rate 63,3%.